Wind power : turbine design, selection, and optimization - Liatkher, V. M. (Viktor Mikhailovich) (Salem, Massachusetts : Scrivener Publishing, 2014)
'Wind power is the most mature technology of the major sources of renewable energy that have been developed, and more efficient and cost-effective techologies and materials are constantly being sought for turbines and the equipment used on them. Here is a comprehensive and thorough review of the engineering pros and cons for using different kinds of wind turbines in different areas, including offshore. With a full technical knowledge, engineers, managers, and other decision-makers in the wind energy industry can make more informed decisions about increasing capacity, cost-efficiency, and longevity. Covering the various types of wind turbines available, such as new collinear windmills, orthogonal turbines, and others, this highly technical treatment of wind turbines offers engineers, students, and researchers insight into the practical applications of these turbines and their potential for maximum efficiency.'--
Includes bibliographical references and index.
Keywords: Wind turbines; Wind power